Learning style of students of Semnan university of medical sciences: A cross sectional study in 2017 - Hassan Babamohamadi; Zahra Sayadjou; Faezeh Daihimfar; Hajar Chahrpashloo; Raheb Ghorbani (Tehran University of Medical Sciences, 2020)
Background & Aim: Some studies across different disciplines have investigated students' learning styles (LS) separately. However, few studies have investigated the LS of students of various educational disciplines in Medical Sciences. We aimed to determine the LS of students of Semnan University of Medical Sciences. Methods & Materials: In this descriptive-cross-sectional study, 228 students of Semnan University of Medical Sciences were selected by cluster sampling in 2017. Data collection tool was the latest version of Kolbchr('39')s learning style inventory. Finally, the data were analyzed by descriptive and analytical (Chi square) tests using the SPSS software version 18. Results: In this study, 54.8% of students were female and 89.5% were single. 63.2% had the average scores higher than 16 and 52.2% were at second semester. The LS of students were assimilation (40.4%), divergent (21.9%), accommodation (19.3%), and convergent (18.4%). There was a significant relationship between the type of LS with the field of study (P=0.014) and average score (P=0.006), but there were no correlations between the type of LS with gender, age, marital status and academic semesters (P>0.05). Conclusion: Considering that the assimilation LS was predominant within the students and given the fact that medical profession is a communicative, people-centered, and practical work, the faculty needs to emphasize the LS of students, and use various teaching strategies to strengthen and enhance the capabilities which are necessary for this group in educational and clinical settings.